Comparison of Brucella canis genomes isolated from different countries shows multiple variable regions (2015)
ABSTRACT: Brucella canis is a pathogenic bacterium for dogs and its zoonotic potential has been increasing in recent years.In this study, we report the sequencing, annotation and analysis of the genome of Brucella canis strain Oliveri isolated from a dog in a breeding kennel in Medellín, Colombia, South America. Whole genome shotgun sequencing was carried out using the ROCHE 454 GS FLX Titanium technology at the National Center for Genomic Sequencing—CNSG in Medellin, Colombia. The assembly procedure was performed using Newbler v2.6. In the genome annotation process, each contig was analyzed independently using as reference Brucella suis ATCC 1330 chromosomes. This new genome could be useful for the development of diagnostic tools and for vaccines search as well, in order to reduce the health impact of this infection in both, dogs and humans. The sequence was deposited in EMBL-EBI with accession numbers HG803175 and HG803176 for chromosomes 1 and 2, respectively.